Trends in Curriculum Changes and their Impact on Integrated Quality Management in Islamic Higher Education - Huzali, Ikhsan; Aimah, Siti; Sidique, Shaufique Fahmi Ahmad (SAINTIS Publishing, 2024)
Curriculum changes in Islamic higher education are a strategic step to answer global challenges and the needs of a growing society. This article examines the trend of curriculum changes that occur in the context of Islamic higher education and its impact on integrated quality management. Through a qualitative approach, this study analyzes various factors that drive curriculum changes, such as technological developments, globalization, and industrial needs. The results of the study show that an adaptive and responsive curriculum not only increases the relevance of education, but also contributes to improving the quality of teaching and learning. The positive impact of this change can be seen in improving academic performance, student engagement, and stakeholder satisfaction. In addition, integrated quality management applied in the curriculum change process is able to create a more effective and sustainable evaluation system. This research recommends the need for collaboration between various parties, including lecturers, students, and the community, to ensure that curriculum changes can be implemented optimally and contribute to improving the overall quality of Islamic higher education.